Measurement of the proton-induced reaction cross-sections of Zr-nat(p,xn)Y-86, Y-87m, Y-87(m+g), Y-88 up to 40 MeV - Khandaker, Mayeen Uddin; Kim, G.; Uddin, M.S.; Lee, Y.S.; Kim, K.; Lee, M. (2008)
We measured the production cross-sections of Y-86, Y-87m, Y-87(m+g), Y-88 radioisotopes for proton-induced reactions on natural zirconium by using a stacked-foil activation technique in the energy range of 4-40 MeV at the MC50 cyclotron of the Korean Institute of Radiological and Medical Sciences. The activation method and the stacked-foil technique using the high-resolution HPGe gamma spectrometry were applied to determine the production cross-sections. The beam current was determined by the monitor reactions Cu-nat(p,x)Zn-62 and Al-27(p,x)Na-22,Na-24. This work reports new data for the above reactions. The results were also compared with ALICE-IPPE model calculations compiled in MENDL-2P file. This experiment is in partial agreement with model calculations. The Optimum energy range for the production of Y-86 is 40 - 30 MeV. The highest yield of Y-86 amounts to 33.37 MBq/mu Ah over this energy range and the levels of the Y-87, Y-87m and Y-88 impurities to 2.3, 26.55 and 0.33 %, respectively at EOB. The Zr-nat(p,x) process may be a suitable route for the production of the medically important radioisotope Y-86.